Merdeka Belajar Kampus Merdeka (MBKM) in Islamic higher education institutions: Ontological, epistemological and axiological reviews - Mawi Khusni Albar; Sangkot Sirait; Sibawaihi (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2024)
This study examines the Merdeka Belajar Kampus Merdeka (MBKM) program in Islamic Higher Education Institutions (PTKI) from ontological, epistemological, and axiological perspectives. The research aims to understand the unique characteristics of MBKM and its impact on Islamic higher education in Indonesia. Employing a qualitative literature review methodology, data were collected through observations and documentation related to MBKM policies and their implementation in PTKI. Data analysis involved data reduction, presentation, and conclusion drawing/verification. Findings indicate that ontologically, MBKM differs from conventional curricula through its flexibility, direct student engagement with real-world contexts, and emphasis on contextual learning. These factors set MBKM apart from more static and rigidly structured curricula. Epistemologically, MBKM is grounded in an educational philosophy that emphasizes academic freedom, innovation, and student involvement in practical activities. This includes curriculum adjustments based on industrial and societal needs, ensuring high relevance and quality of education. Axiologically, MBKM significantly enhances students' practical skills and soft skills, such as critical thinking, problem-solving, and collaboration. The program's relevance is evident in bridging the gap between theory and practice, and between education and industry. Benefits of MBKM include improved graduate employability, expanded professional networks, and tangible contributions to national development through humanitarian and entrepreneurial projects. These advantages highlight MBKM as an adaptive and responsive educational model to global changes. The study concludes that MBKM has significant potential to enhance the quality of higher education at PTKI and contribute substantially to societal development.